2024
DOI: 10.1017/qpb.2024.1
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis leaf quantitative atlas: a cellular and subcellular mapping through unified data integration

Dimitri Tolleter,
Edward N. Smith,
Clémence Dupont-Thibert
et al.

Abstract: Quantitative analyses and models are required to connect a plant’s cellular organisation with its metabolism. However, quantitative data are often scattered over multiple studies, and finding such data and converting them into useful information is time-consuming. Consequently, there is a need to centralise the available data and to highlight the remaining knowledge gaps. Here, we present a step-by-step approach to manually extract quantitative data from various information sources, and to unify the data forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…The quantification of anatomical traits is of fundamental importance for recent efforts in crop improvement and the generation of cell– and tissue atlases (Lee et al ., 2023; Tolleter et al ., 2024). Anatomics MLT will provide a useful tool for gathering large-scale input data.…”
Section: Discussionmentioning
confidence: 99%
“…The quantification of anatomical traits is of fundamental importance for recent efforts in crop improvement and the generation of cell– and tissue atlases (Lee et al ., 2023; Tolleter et al ., 2024). Anatomics MLT will provide a useful tool for gathering large-scale input data.…”
Section: Discussionmentioning
confidence: 99%
“…As mesophyll cells do not appear to have unique cell type markers 44 , we relied on the observation that they instead are enriched for proteins involved in photosynthesis (LHCs) and carbon fixation (RuBisCo). Indeed, it has been demonstrated that the fractional volume occupancy of chloroplasts in mesophylls is much higher (9.3% for mesophyll palisade and 15.5% for spongy mesophyll) than epidermal cells (0.45% for abaxial and 0.22% for adaxial) 45 . In agreement with the high-volume chloroplast occupancy in the mesophyll cell type, we observe LHC and RuBisCo proteins represent up to 46% of protein copies on average in well-watered protoplasts in this study.…”
Section: Discussionmentioning
confidence: 99%